Evaluation of the physico-chemical stability of the adapted oral pharmaceutical form of mycophenolate mofetil - Livian Nathaly GRESELE; Gisele Mendes SOUZA; Juliane CARLOTTO; Lauro Mera SOUZA; Alan Almeida VEIGA; Klézia Morais BELLETTI (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde)
Objective: To evaluate the physicochemical stability of the adapted oral suspension of mycophenolate mofetil tablets developed by a university hospital in Paraná, in order to determine the concentration of the active ingredient present in the oral suspension over time, assess the homogeneity of the drug concentration during the administration of the doses and establish a shelf life consistent with the stability of the adapted pharmaceutical form. Method: Mycophenolate mofetil tablets were used to make suspensions in two different concentrations - 50 mg/mL and 100 mg/mL - using sorbitol and water as vehicles (1:1) and adding a flavoring agent. The chromatographic analysis of the samples was carried out at times (T): T0h, T24h, T48h, T120h and T168h. The chromatographic conditions used for high-performance liquid chromatography were adapted from the United States Pharmacopeia. Results: The average relative standard deviation of the three batches analyzed at each time and concentration ranged from 6 to 18%, establishing an acceptable variability in the data obtained, but signaling the inhomogeneity of the active in the suspension. In the chromatographic analysis, the drug concentration values obtained in the formulations were satisfactory for all the times analyzed, with the values for T0h, T24h, T48h, T120h and T168h being 100%, 99.3%, 97.2%, 106.6% and 96.8% respectively. No physical changes were observed during the análisis period. The formulation showed physicochemical stability in an amber glass bottle, protected from light and at room temperature for 7 days. Conclusion: It was possible to validate the stability of the proposed formulations for seven days at room  emperature and in an amber glass bottle. It is important to develop further studies on oral liquid formulations adapted from mycophenolate mofetil tablets.